Measuring the Impact of Social, Economic and Environmental Challenges on Sustainable Development - Gabriel Croitoru; Nicoleta Valentina Florea; Daria Florea; Mihai Bogdan Croitoru; Brândușa Adriana Dragomir (Revista de Studii Financiare)
In the context of today’s global challenges, sustainable development is becoming a primary objective for governments around the world. This article analyses the synergies and divergences between social, economic and environmental policies and their impact on sustainable development. The study was conducted on a sample of 220 respondents, selected through stratified sampling methods to ensure representativeness and a comprehensive picture of the perceptions and experiences of different population segments. The research method used was the modelling of partial structural equations (PLS-SEM), implemented with the help of the SmartPLS 4.06 software, which allowed the examination of the direct and indirect relationships between the studied variables: social policies (SP), economic policies (EP), environmental policies (PM), quality of life (CV), social equity (ES) and sustainable development (DD). This study contributes to the understanding of synergies and divergences in the management of social, economic and environmental challenges, highlighting the importance of an integrated approach in public policy formulation to promote sustainable development. The limitations of the study include the subjectivity of the data collected and the specific geographic context, suggesting the need for further research to explore intermediate variables and expand the study context.